Experimental and theoretical study of ZrMo-KIT-6 solid acid catalyst with abundant Brønsted acid sites. Issue 15 (24th March 2022) - Mu, Jinglin; Liang, Manfen; Huang, Hong; Meng, Jian; Xu, Leilei; Song, Zhiling; Wu, Mei; Miao, Zhichao; Zhuo, Shuping; Zhou, Jin
Abstract : Synergistic effect of Zr and Mo species in the formation of Brønsted acid sites is investigated by experimental and theoretical study. Abstract : Given their excellent reusability and environmental friendliness, solid acid catalysts have drawn considerable attention in acid-catalyzed reactions. However, the rational design and synthesis of solid acid catalysts with abundant Brønsted acid sites remains a challenge. In this paper, KIT-6, Zr-KIT-6, Mo-KIT-6, and ZrMo-KIT-6 solid acid catalysts are designed and synthesized. The textural properties, chemical bonds, and acidic properties of these catalysts are explored. Theoretical calculations are conducted to explore the formation mechanism of Brønsted acid sites. The theoretical trend of acidity is consistent with the experimental result of acidity and further demonstrates that the synergistic effect of Zr and Mo species improves the formation of Brønsted acid sites. The as-obtained ZrMo-KIT-6 solid acid catalysts are employed in Friedel–Crafts benzylation reaction, and the outstanding catalytic performance of the ZrMo-KIT-6 catalyst indicates that it is an excellent Brønsted solid acid catalyst.